Perinatal treatment of parents with the broad-spectrum antibiotic enrofloxacin aggravates contact sensitivity in adult offspring mice - Kowalczyk, Paulina (Pharmacol Rep, 2021)
BACKGROUND: Antibiotics, while eliminating pathogens, also partially deplete commensal bacteria. Antibiotic-induced dysbiosis may contribute to the observed rise in “immune-mediated” diseases, including autoimmunity and allergy. The aim of this study is to investigate the impact of perinatal antibiotic treatment on T cell-mediated immune response in adult mice. METHODS: Oral treatment with broad-spectrum antibiotic enrofloxacin during gestation and breastfeeding or breastfeeding or gestation alone was used to evaluate whether antibiotic exposure early in life could modulate contact sensitivity (CS) in adult mice. RESULTS: Here, we demonstrated that enrofloxacin treatment during gestation and breastfeeding, but not during pregnancy or breastfeeding alone, aggravated CS reaction in adult mice measured by ear swelling. These data correlate with increased myeloperoxidase (MPO) activity in the ear extracts and elevated production of IL-6 and IL-17A by auricular lymph node cells (ELNC) and was not influenced by food consumption and body weight. In each dosing regimen, enrofloxacin treatment reduced the relative abundance of Enterococcus spp. but did not influence the relative abundances of Lactobacillus, Clostridium cluster XIVa, XIVab, I, Bacteroidetes, and segmented filamentous bacteria (SFB). However, prolonged enrofloxacin-treatment during both gestation and breastfeeding decreased the relative abundance of Clostridium cluster IV. CONCLUSION: These data show that long-term perinatal enrofloxacin treatment induces intestinal dysbiosis, characterized by decreased levels of anti-inflammatory Clostridium cluster IV, and alters T cell-dependent immune responses, enhancing CS reaction in adult mice.